Physicochemical properties, antioxidant and antibacterial activities of honey produced by Heterotrigona itama and Tetragonula laeviceps - Dewi Cakrawati; Zulfikar Fadhil; Trisya Nur Adzni Destianti (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Honey is a popular healthy food that also serves as medicine. Stingless bee honey gained interest compared to regular honey due to its health benefits. This study aimed to investigate the potential health benefits of honey produced by stingless bees Heterotrigona itama and Tetragonula laeviceps, namely phenolic content, flavonoid content, antioxidant capacity, and antimicrobial activity. The research was conducted using complete randomized experimental design by two separate replications. The result shows both honeys have a pH value ranging from 3.16 to 3.43. The antioxidant capacity, total phenolic compounds, and total flavonoid compounds of both honeys were not different (p≥ 0.05). The antioxidant capacity of honey produced by Heterotrigona itama and Tetragonula laeviceps was 593 mg TE/100 and 581.58 mg TE/100 g, respectively. The total phenolic compound was in the range of 839.26-1242 mg GAE/kg, while total flavonoid was in the range 126 – 179 mg QE/ of) However, H.itama honey had the highest inhibition against Gram-positive Streptococcus mutans, while T.laeviceps had the highest inhibition against Gram-negative Pseudomonas aeruginosa. The types of local vegetation might relate to phytochemical compounds in honey. This study gave insight into another possible antibacterial compound in stingless bee honey, namely, a bioactive peptide that might act differently on microorganisms.